Superalloys 1992 (Seventh International Symposium) 1992
DOI: 10.7449/1992/superalloys_1992_487_496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment and Chemistry on the Long-Term Phase Stability of a High Strength Nickel-Based Superalloy

Abstract: Phase stability of UDIMET@ alloy 720 (U720), a high strength, @ Registered Trademark of Special Metals Corporation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 2 publications
3
27
0
1
Order By: Relevance
“…It was possible to show that the somewhat minor change in composition of U720 to U720LI would cause a sharp drop in stability, consistent with the experimental results of Keefe et al [32]. However at that time it was not possible to calculate the TTT diagram.…”
Section: During Solidificationsupporting
confidence: 78%
See 1 more Smart Citation
“…It was possible to show that the somewhat minor change in composition of U720 to U720LI would cause a sharp drop in stability, consistent with the experimental results of Keefe et al [32]. However at that time it was not possible to calculate the TTT diagram.…”
Section: During Solidificationsupporting
confidence: 78%
“…However at that time it was not possible to calculate the TTT diagram. This has now been achieved and Figure 9 shows the calculated results with the experimental observations of Keefe et al [32]. The results match the different behaviour of the two alloys rather well.…”
Section: During Solidificationsupporting
confidence: 70%
“…The exponent ndBr takes 3 which is identical value in equation (1). Figure 6 shows the predicted average grain size and actual observed one in case of pancake forging.…”
Section: Modelinementioning
confidence: 57%
“…However, experience has shown that a level of 18 wt.% in alloy 720 causes excessive precipitation of σ and µ phases after relatively short exposure times above 700ºC 2,11 . Since these phases are known to degrade the creep properties of nickel disc alloys 12,13 , a balance between improved fatigue crack growth resistance and reduced TCP phase formation was struck at around 15 wt.% chromium.…”
Section: Alloy Compositionmentioning
confidence: 99%